(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Education is intimately connected to the growth and well-being of people all around the world. Education in all of its many manifestations—physical, mental, psychological, and spiritual—is necessary for the development of individuals as well as nations. This holds true across the board. While the realisation of one's divine consciousness and serving as a conduit for the expression of that awareness is the overarching goal of all types of education, the specific aim of spiritual education is to make it possible for individuals to lead lives that are meaningful. Sadly, in today's society, spiritual education is not given nearly as much importance as it should be, despite the fact that it plays an important role in improving people's mental health. It is crucial that we follow the counsel of visionaries and educators who emphasise the significance of spiritual education if we are to stop humanity from veering off of the path it is on. This will prevent humanity from straying from the path it is on. In this article, Aurobindo Ghosh's perspectives on spiritual education, its aims, and their relevance in today's world are subjected to an in-depth analysis and critique.